2012
DOI: 10.1021/jp308334x
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy of Enhancing the Photoactivity of g-C3N4via Doping of Nonmetal Elements: A First-Principles Study

Abstract: An effective structural doping approach has been described to modify the photoelectrochemical properties of g-C 3 N 4 by doping with nonmetal (sulfur or phosphorus) impurities. Here, the substitutional and interstitial doped models of g-C 3 N 4 systems were constructed with different doped sites, and then their dopant formation energies and electronic properties were performed to study the stability and visible-light photoactivity using firstprinciples density functional theory, respectively. Our results have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
338
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 634 publications
(393 citation statements)
references
References 60 publications
37
338
0
2
Order By: Relevance
“…For P O C 3 N 4 , the PL intensity decreases sharply. On the one hand, the calculation results showed that phosphorus doping can increase the dispersion of the contour distribution of HOMO and LUMO, which improves the carrier mobility [23]. The noncoplanar HOMO and LUMO favors the separation of photogenerated electron-hole pairs, decreasing the recombination rate.…”
Section: Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…For P O C 3 N 4 , the PL intensity decreases sharply. On the one hand, the calculation results showed that phosphorus doping can increase the dispersion of the contour distribution of HOMO and LUMO, which improves the carrier mobility [23]. The noncoplanar HOMO and LUMO favors the separation of photogenerated electron-hole pairs, decreasing the recombination rate.…”
Section: Catalystmentioning
confidence: 99%
“…For P O C 3 N 4 , the absorption edge further shifts to 494 nm, corresponding to the band gap energy of 2.51 eV. Ma et al academic calculated the electronic structure of phosphorus doped g-C 3 N 4 using first-principles [23]. They found an isolated P 3p state is localized just 0.15 eV below the bottom of the CB of the host g-C 3 N 4 , leading to the decreased band gap energy.…”
Section: Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…g-C 3 N 4 doping is a common strategy to broaden spectral utilization and band alignment to drive separate photogenerated charge carriers. Doping by metals such as Cu and Fe [224][225][226], non-metals such as B, C, O, or S [224,[227][228][229][230][231], and co-doping [232][233][234] have all been employed for environmental depollution applications. For example, S and O co-doped g-C 3 N 4 prepared by melamine polymerization and subsequent H 2 O 2 activation prior to trithiocyanuric acid functionalization (Figure 21a) enhanced the photocatalytic degradation of RhB (Figure 21b) 6-fold relative to the parent g-C 3 N 4 nanosheet [235].…”
Section: Environmental Remediationmentioning
confidence: 99%
“…However, the catalytic efficiency is quite low due to the high recombination rate of excited charge carriers. As a result, advancement of g-C 3 N 4 structure is extremely desired to avoid this shortcoming and mainly associates with the construction of mesoporous structure [23,24], doping with metal or nonmetal elements [25][26][27][28], composting with other semiconductors [29][30][31][32][33], and exfoliation of bulk form into nanosheets [34][35][36][37]. In particular, the exfoliation of bulk g-C 3 N 4 to nanosheets is able to reduce the edge thickness and create new exposed surface, easily leading to the enlarged specific surface area, enhanced charge carriers motilities through reduced migration distances, and variable conduction and valence band positions, which is favorable to the enhancement of photocatalytic performance [34,36].…”
Section: Introductionmentioning
confidence: 99%